Impact of miRNAs in the pathoetiology of recurrent implantation failure - Mohadeseh Fathi; Mohammad Amin Omrani; Sepideh Kadkhoda; Akram Ghahghaei-Nezamabadi; Soudeh Ghafouri-Fard (Molecular and Cellular Probes, 2024)
Recurrent implantation failure (RIF) is a condition with a multifactorial basis. Recent research has focused on the role of genetic factors in the pathophysiology of RIF. Of particular note, miRNAs have been found to contribute to the pathogenesis of RIF. Several miRNA polymorphisms have been investigated in this context. Moreover, dysregulation of expression of a number of miRNAs, including miR-374a-5p, miR-145-5p, miR-30b-5p, miR-196b-5p, miR-22, miR-181 and miR-145 has been found in RIF. This review concentrates on the role of miRNAs in RIF to help in identification of the molecular basis for this condition and design of more effective methods for management of RIF, especially in a personalized manner that relies on the expression profiles of miRNAs in the peripheral blood or endometrium.